Improving the Quality of Healthcare Services for Patient well-being through Maqaṣid al-Sharia: a Study at Klaten Islamic Hospital - Muhammad Uqbah Azis; Jaih Mubarok; Nur Kholis; Setiyawan Gunardi (Institut Agama Islam Negeri (IAIN) Manado, 2026)
Non-Indexed Publication